From Fragmentation to Integration: Public Space Reconfiguration of Shanghai Rail Transit Baoshan Road Transfer Station - FANG Yingli; ZHANG Yingxin; JIN Yanlin; ZHANG Bin; XU Peipei; WANG Jinkun (Chengshi guidao jiaotong yanjiu)
[Objective] To analyze the impact of urban rail transit infrastructure transformation on urban public space and its integration strategies, it is necessary to investigate the preconditions and specific requirements for urban rail transit station transformation projects, while revealing the complex relationship between urban public space and infrastructure. [Method] Taking Baoshan Road Station of Shanghai Metro Line 3 and Line 4 as a case study, the structure of the existing station space, on-site mapping of critical platform nodes and user experience are analyzed. Focusing on the public space fragmentation phenomenon of Baoshan Road Station, demonstration is conducted from aspects of "artificial chasms" administrative boundaries, discontinuity in external traffic organization and fragmentation of internal passenger flow lines. A multi-scale integration strategy is proposed. [Result & Conclusion] At Baoshan Road Station, the management segmentation formed by administrative boundaries intensifies public space fragmentation; insufficient external traffic organization planning leads to poor multi-modal traffic linkages; the design of in-station passenger flow line leads to unnecessary detours and congestion, degrading the passenger experience. The multi-scale integration strategy is: at the rail transit scale, optimizing the station functional area and the passenger flow line; at the citizen scale, focusing on the space pedestrian friendliness and improving public service facilities; attempting to build the infrastructure into buildings and improving the overall station image through a unified design language; continuing the urban context and strengthening the recognition and sense of belonging of the public space by implanting cultural elements. The transformation of rail transit stations is not only an optimization of infrastructure, but also an important opportunity to improve the quality of urban public space. It needs to be considered comprehensively from multiple dimensions to achieve the coordination and unity of function and culture.